206 Dynamic Stimulation of Human Visual Cortex Produces Useful Percepts of Visual Forms in Sighted and Blind Subjects. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Yoshor, Daniel; Bosking, William H; Foster, Brett L; Sun, Ping; Niketeghad, Soroush; Sheth, Sameer A; Greenberg, Robert; Pouratian, Nader; Beauchamp, Michael S
Abstract: INTRODUCTION: Visual cortical prosthetics (VCPs) aim to restore vision to the blind by bypassing irreparably damaged eyes or optic nerves and directly activating visual cortex. Previous experiments have demonstrated that electrical stimulation of retinotopic visual cortex can elicit percepts of spots of light known as phosphenes, but have failed to demonstrate that multiple phosphenes can be combined into percepts of coherent visual forms. Here we show initial results with dynamic current steering, a novel strategy for producing useful percepts of visual forms with a VCP. METHODS: Dynamic current steering contains 2 components. The dynamic stimulation component refers to rapidly sweeping electrical stimulation across the retinotopic map in a pattern that corresponds to the desired visual object. This dynamic sweeping combines the individual phosphenes into a unified percept. The current steering component refers to concurrently stimulating combinations of electrodes to produce activation at arbitrary locations between them, allowing us to create virtual electrodes that approximate a more continuous trajectory. RESULTS: We tested dynamic current steering using semichronically implanted cortical surface electrodes in 6 sighted patients undergoing clinical monitoring for epilepsy, as well as in 1 blind subject implanted with a chronic electrode array for a VCP feasibility study. With limited training, both sighted and blind subjects could reliably identify and distinguish between simple letter/number graphemes produced with dynamic current steering patterns based on retinotopic and phosphene maps. In contrast, simultaneous multi-electrode stimulation (the conventional stimulation paradigm) never resulted in a percept of a grapheme. CONCLUSION: Our results demonstrate that dynamic current steering applied to human visual cortex can consistently produce behaviorally useful percepts of visual forms. When combined with extensive subject training and higher resolution electrode arrays, this promising stimulation paradigm may enable forthcoming VCPs to restore meaningful visual function to the blind, including recognition of visual forms and visual navigation.